Preparation of novel ceramic membranes modified by mesoporous silica with 3-aminopropyltriethoxysilane (APTES) and its application to Cu2+ separation in the aqueous phase - Oh, Seogil; Kang, Taewook; Kim, Honggon; Moon, Jungwoo; Hong, Surin; Yi, Jongheop (ELSEVIER SCIENCE BV, 2007)
A chemically active inorganic membrane with an ordered mesoporous skin layer was used for separation Of Cu2+, in an aqueous solution. Mesoporous silica was deposited on the surface of a ceramic membrane using an anionic polyelectrolyte (poly(sodium 4-styrene sulfonate)) as an intermediate layer. A strong anionic polyelectrolyte was used to reduce electrostatic repulsion between the membrane surface and mesoporous silica under acidic (pH <= 1) conditions. Next, to provide the membrane and mesoporous skin layer with the ability to reject Cu2+, ions, 3-aminopropyltriethoxysilane (APTES) was grafted onto the surface of the mesoporous skin layer. This modified membrane (CM-MA) was characterized by FE-SENI, TEM and FT-IR. The CM-MA showed a much higher total rejection value (87.08%) than that of the untreated membrane (6.09%). In addition, the CM-MA exhibited a highly selective separation capability for Cu2+ ions in the presence of equimolar amounts of other metal ions (Ni2+, Pb (2+)). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: FILMS; SURFACE; GAS; NANOCOMPOSITES; SPECTROSCOPY; COPOLYMER; ADSORBENT; TRIBLOCK; SUBLAYER; REMOVAL